Box Model Intercomparison of Cloud Chemistry. Issue 21 (4th November 2021) - Barth, Mary C.; Ervens, Barbara; Herrmann, Hartmut; Tilgner, Andreas; McNeill, V. Faye; Tsui, William Gang; Deguillaume, Laurent; Chaumerliac, Nadine; Carlton, Annmarie; Lance, Sara M.
Abstract: Chemical processes in clouds and fogs can substantially alter atmospheric oxidant budgets and lead to aerosol mass formation. However, many regional and global models do not include detailed aqueous‐phase chemical mechanisms due to the (a) lack of complete understanding of the chemical processes and (b) computational burden of adding constituents. Current gas‐aqueous chemistry 0‐dimensional models were evaluated in a cloud‐chemistry box model intercomparison based on a mid‐September 2016 cloud chemistry event at Whiteface Mountain, New York. Multiphase mechanisms in the five participating models ranged from those appropriate for 3‐d models to highly complex with thousands of reactions. This study focused on oxidant levels in both phases and aqueous‐phase sulfate and organic acid formation. Comparison of gas‐phase‐only chemistry gives very similar oxidant predictions at night but shows significant differences during daytime with the hydroxyl radical (OH) variability of about an order of magnitude. The variability in the model results increases substantially with aqueous chemistry due to different Henry's Law constants, aqueous‐phase reaction rate constants, and chemical mechanisms. Using a prescribed liquid water content and pH value of 4.5, modeled aqueous OH, aldehyde, and organic acid concentrations differ by over an order of magnitude in daytime. Simulations were also conducted at a pH = 5.1, predicted variable pH, and with added transition metal ion chemistry. While we compare predicted and measured inorganic anions and water‐soluble organic carbon, we cannot do so for aqueous‐phase oxidant concentrations due to the lack of measurements. We highlight a need for recommended equilibrium and aqueous‐phase rate constants. Plain Language Summary: Accurate description of cloud chemistry is needed in models used to predict air quality and climate. A comprehensive international cloud box model intercomparison with physical and chemical observational constraints from mountain top sampling highlights the need for a concerted effort to develop robust aqueous‐phase chemical mechanisms. Prediction of some key species differ among the models by orders of magnitude. We investigate the underlying, fundamental chemical explanations for the discrepancy as a diagnosis to understand the chemical parameters most in need of further investigation efforts. Key Points: Five box models participated in a cloud chemistry intercomparison representing a case at Whiteface Mountain Observatory Model results were often quite different indicating a need for recommended equilibria and aqueous‐phase reaction rate constants Comparisons of simple to detailed chemistry schemes show need for development of effective simplified organic aqueous chemistry schemes